2011
DOI: 10.4248/ijos11033
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of interspecies adherence of oral bacteria using a membrane binding assay coupled with polymerase chain reaction‐denaturing gradient gel electrophoresis profiling

Abstract: Information on co-adherence of different oral bacterial species is important for understanding interspecies interactions within oral microbial community. Current knowledge on this topic is heavily based on pariwise coaggregation of known, cultivable species. In this study, we employed a membrane binding assay coupled with polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) to systematically analyze the co-adherence profiles of oral bacterial species, and achieved a more profound knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…polymorphum adhesin RadD by the S. mutans adhesin SpaP (Guo et al, 2017). Thus, the RaD/SpaP adhesin pair serves as a binding mechanism for fusobacteria and implies their high virulence potential, since S. mutans interacts with only a limited number of other bacterial species (Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…polymorphum adhesin RadD by the S. mutans adhesin SpaP (Guo et al, 2017). Thus, the RaD/SpaP adhesin pair serves as a binding mechanism for fusobacteria and implies their high virulence potential, since S. mutans interacts with only a limited number of other bacterial species (Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as dental biofilm formation is a dynamic process (Wang et al 2011), and with more than 600 bacterial species identified from the oral cavity, further study is required to determine whether the inhibitor can affect the complicated bacterial interactions between dental biofilm microorganisms. The impact of compound 5H6 on biofilm biology also requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first time a cognate adhesin pair was identified for attachment of a fusobacterial species to another organism. Streptococcus mutans does not interact with a large number of other bacterial species, but it is an interesting phenomenon that the ubiquitous fusobacteria, which are known to bind to numerous other microorganisms, recognize at least two different surface structures on S. mutans for attachment. This could possibly expand their own ability as well as that of S. mutans to effectively colonize available oral surfaces.…”
Section: Discussionmentioning
confidence: 99%